Rheological and structural properties of dilute active filament solutions - Ziebert, Falko; Aranson, Igor S. (Physical review. E, Statistical, nonlinear, and soft matter physics, 2008)
The rheology and the structure of a dilute semiflexible biofilament solution, like F-actin, interacting via molecular motors is probed by molecular dynamics simulations. Oscillatory external shear is used to measure the storage and loss moduli as a function of motor activity in a range of frequencies and for low shear rates. The overall effect of the motor activity on the rheological properties is interpreted as an increase of the temperature, with the effective temperature proportional to the density of motors. However, the effect of motors on the structural properties of the solution, such as the orientation correlation function, is opposite: the motors drastically increase the orientation correlation length whereas thermal fluctuations decrease it.
Gesehen am 21.09.2022